Peripheral issues in combined event and multi-event training design - Schexnayder, B. (Techniques Magazine, 2018)
In this chapter taken from the combined events specialist certification course curriculum, many of the peripheral issues that impact an athlete´s development are addressed. Topics include record keeping, testing, rest and restoration and lifestyle issues among others.